Synthesis and ring-opening polymerization of 2-substituted 1, 3-benzoxazine: the first observation of the polymerization of oxazine ring-substituted benzoxazines. Issue 46 (9th November 2016) - Ohashi, Seishi; Cassidy, Francis; Huang, Stephanie; Chiou, Kevin; Ishida, Hatsuo
Abstract : 2-Substituted 1, 3-benzoxazines having a phenyl group as an oxazine ring substituent are synthesized with benzaldehyde through 2-hydroxy- N -phenylbenzylamine structures. Abstract : 2-Substituted 1, 3-benzoxazines (two benzoxazine monomers used in this paper are abbreviated asPH-a- [2]ba andPH-pda- [2]ba ) having a phenyl group as an oxazine ring substituent are synthesized with benzaldehyde through 2-hydroxy- N -phenylbenzylamine structures. The polymerization of these monomers is observed for the first time and confirmed using differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FT-IR). The poly(PH-a- [2]ba ) derived from 2-substituted 1, 3-benzoxazines exhibits good thermal properties based on TGA analysis, despite showing slight inferiority to poly(PH-a ), an unsubstituted counterpart ofPH-a- [2]ba . Additionally, benzylideneaniline is extracted during the polymerization, indicating that this compound is the byproduct of the polymerization mechanism. Structural verification is achieved by synthesizing benzylideneaniline and comparing its 1 H-NMR spectrum with the reaction byproduct.